Soft skill improvement for Seruni Foundation foster children - Dani Ramdani; Ganjar Garibaldi; Bimbim Magh (Jurnal Pemberdayaan: Publikasi Hasil Pengabdian Kepada Masyarakat, 2021)
The lack of financial literacy, the low level of social skills, and the low self-confidence of Seruni Foundation children are the backgrounds of this service program being implemented. This program aims to provide training on developing and improving soft skills and financial skills for Seruni Foundation children. The specific target to be achieved is to be able to improve soft skills and financial skills in Seruni Foundation children such as having a spirit of competitiveness, adaptive and anticipatory, open to change, able to learn, skilled, easy to adapt to new technology, literate about finances and budgets and having a strong foundation of the ability to develop. The method used is to provide consultation and training. The parties involved in this program are consist of lecturers in the fields of finance and organizational behaviour, in collaboration with a foundation that manages the Seruni Foundation children for 14 hours divided into two days. With the training provided by the team, Seruni Foundation children have become more developed, more confident, understand how to manage finances properly and are able to compete in the business and industrial world